Performance of Grain Cleaner APB-M1 in Cleaning of Maize Grain - Tabran M. Lando; Yamin Sinuseng; Ramlah Arief (PERTETA, 1999)
The research to evaluate perfornlance of grain cleaner APB-MI was conducted in the Research Institute for Maize and Other Cereals tit the beginning of 1998. Five engine circles were tested: 1200, 1350, 1500, I650 and 1800 rpm with three replications. Bisma variety was used us maize grrrin with 13% moisture content (wet basis) and for each replication the amount was 25 kg. The results showed that power transmission efficiency was at the average of 95.0% on the strainer and 94.2% on the blower. Fuel conszrtnptionwas at the rate of 0,81 //hour with average cleaning capacity of 598 kg/hour.